Novel aqueous two-phase systems based on tetrahydrofuran and potassium phosphate buffer for purification of lipase - Souza, Ranyere L.
Aqueous two-phase systems (ATPS) based on tetrahydrofuran (THF) + potassium phosphate buffer (pH 7) were used in this work for the purification of lipases. Binodal curve, tie lines and critical point were obtained for the new THF-salt ATPS at 25 degrees C and the binodal curve were successfully correlated with the Merchuck and Hu equations. To optimize the extraction capability of this ATPS the effects of the concentration of components and temperature of equilibrium on the partition coefficients and extraction efficiencies were investigated using lipase from Burkholderia cepacia (commercially obtained) as a model compound. The optimum conditions for the purification of an extracellular lipase obtained by submerged fermentation were established through a surface response analysis by central composite rotational design applied allowing a purification factor (PF) of 103.9 +/- 0.9 and an enzyme recovery of 96.4 +/- 1.1 achieved using this process. Moreover, a commercial lipase by Candida antarctica B recombinant in Aspergillus niger was purified (PF= 4.84 +/- 0.24), confirming the potential of this new THF-based ATPS for purifying lipases. (C) 2015 Elsevier Ltd. All rights reserved.